STUDI KOMPARASI PRESTASI BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE TSTS DAN TPS PADA POKOK BAHASAN STRUKTUR ATOM DAN SISTEM PERIODIK UNSUR DI KELAS XI IPA SMA NEGERI 5 PEKANBARU - Hasanah, Fitriatul; Erna, Maria; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Has conducted a comparative study to find out significant differences in studentâs achievement and to determine studentâs achievement higher between implementation of cooperative learning models TSTS and TPS on learning topic of Atomic Structure and Elements of the Periodic System at SMAN 5 Pekanbaru. This is an true experimental research with Design Randomized Control Group Pretest-Posttest. The research sample consisted of 2 experimental classes with the implementation of cooperative learning models TSTS and TPS, and 1 control class. Research data analysis using ANOVA one way followed by Scheffe multiple comparison test. Based on the results of data processing by ANOVA one way obtained that Fcount > Ftable is 15,37 > 3,08 which shows that there are significant differences in student achievement between the experimental class TSTS, TPS, and control class. The results of data processing by Scheffe multiple comparison test was obtained the difference between the average experimental class of TSTS and TPS exceeded the values Scheffe is 4,79 > 4,68 and an average experimental class of TSTS higher than average experimental class of TPS is 54,1 > 49,31 which shows that there are significant differences in studentâs achievement between implementation of cooperative learning models TSTS and TPS. Studentâs achievement with implementation of cooperative learning models TSTS higher than TPS on learning topic of Atomic Structure and Elements of the Periodic System in class XI IPA SMAN 5 Pekanbaru.Keywords: TSTS, TPS, Learning Achievement, Atomic Structure and Elements of the Periodic System